واقع تجارة بيع الأحذية عبر موقع الأنستغرام دراسة ميدانية على عينة من تجار محلات بيع الاحذية عبر موقع الانستغرام بولاية الاغواط - ليلى وانس; مليكة بن عيسى; معاش طيب (My University, 2023)
Trade has been known through many centuries and various developments, and perhaps what distinguishes this activity in today’s era is the growing role of technology and the pursuit of maximum benefit from its benefits to practice a modern style of exchanges known as electronic commerce, which has emerged as a modern method for presenting goods and services and making deals electronically. This trade has been able to spread widely In a short time, its importance increased and gained general acceptance, as it took its place in international trade relations faster than expected. Electronic commerce has become a reality not only in developed countries, but also in all parts of the world